Comparing the Effectiveness of Exercise, Antidepressants, and Their Combination in Treating Mild Depression: Systematic Review - Fransisca; Evelyn (International Medical Journal Corp. Ltd, 2024)
Background: Depression is a prevalent condition affecting over 320 million people worldwide and is a leading cause of disability. Although second-generation antidepressants are commonly prescribed, their effectiveness, particularly for non-severe depression, is controversial. Alternative treatments, such as exercise, have gained attention for their potential benefits. Objectives: This systematic review aims to compare the effectiveness of exercise and antidepressants on depressive symptoms in adults with non-severe depression. Additionally, it explores the effects of combination treatment versus monotherapy and examines drop-out rates to gauge treatment acceptance. Methods: Adhering to PRISMA 2020 guidelines, studies published in English between 2014 and 2024 were reviewed. Databases searched included PubMed, Science Direct, and SagePub. Eligible studies focused on the comparative effectiveness of exercise and antidepressants for non-severe depression. Results: The review included five relevant studies. Findings suggest that exercise can be a beneficial adjunctive treatment for depression, improving both mental health and physical fitness. Conclusion: Exercise is a promising non-pharmacological treatment for non-severe depression, with evidence supporting its efficacy. Further comprehensive trials are needed to establish definitive guidelines and long-term benefits.